2002
DOI: 10.1109/6144.991176
|View full text |Cite
|
Sign up to set email alerts
|

On the mode II popcorn effect in thin packages

Abstract: Experiments were carried out using P-TQFP-176 packages to study the mode II popcorn effect in thin packages. The doming of the package backside was measured as a function of time and temperature. The measurements were performed using a line projection method. An "accelerated" increase in the doming was found to correlate with the onset of the package crack propagation. It was shown that when a constant critical doming angle is reached, package cracks begin to propagate toward the surface. This critical doming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Experimental studies on type II package cracking have shown that plastic packages could fail by interface delamination and/or rupture of the die-attach layer (e.g. Alpern et al, 2002;Tay and Lin, 1999;Pang and Seetoh, 1997;Pang et al, 2002). The numerically simulated behaviors are consistent with these experimentally observed failure mechanisms.…”
Section: Discussionsupporting
confidence: 81%
“…Experimental studies on type II package cracking have shown that plastic packages could fail by interface delamination and/or rupture of the die-attach layer (e.g. Alpern et al, 2002;Tay and Lin, 1999;Pang and Seetoh, 1997;Pang et al, 2002). The numerically simulated behaviors are consistent with these experimentally observed failure mechanisms.…”
Section: Discussionsupporting
confidence: 81%
“…Several models have been used to predict the relationship between viscosity (µ) and the degree of polymerization. The Castro-Macosko model has been applied by Nguyen et al [8] and Alpem et al [9] is selected to use in this simulation. It is described as follows:…”
Section: Research Methods 21 Mathematical Modelmentioning
confidence: 99%
“…The temperatures from this analysis can be mapped onto a stress analysis to give the moisture-stress, using the coefficient of moisture expansion is given in place of the coefficient of thermal expansion. This method has been used frequently and is widely documented [3][4]. The limitation of this approach is that it ignores any effect of temperature gradient or pressure on the moistures distribution.…”
Section: Introductionmentioning
confidence: 99%